Correlation between moderate to vigorous physical activity levels and cardiovascular disease in middle-aged and elderly people - Mengya HE; Lan LI (Guangxi Yike Daxue xuebao, 2025)
Objective To investigate the correlation between moderate to vigorous physical activity (MVPA) levels and cardiovascular disease (CVD), so as to provide a basis for the prevention and control of CVD. Methods Data for this study were obtained from the China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2020. A cohort of 6, 100 middle-aged and elderly people with data on physical activity and cardiovascular status was included. Logistic regression modeling was used to explore the association between MVPA and CVD, and subgroup analyses were conducted for age and gender. Results The amount of MVPA in the population with CVD was significantly lower than that in the normal population (5, 040 MET min/week vs 6, 160 MET min/week, P < 0.001). After adjusting for confounding factors, for every one quartile increase in MVPA, the risk of developing CVD was decreased by 13.2% (OR=0.868, 95% CI: 0.765-0.985). Moreover, there was a non-linear dose- response relationship between MVPA and the risk of new-onset CVD (Poverall < 0.05, Pnonlinearity < 0.10), and the inflection point for the risk of new-onset CVD was 5, 674.47 MET min/week. When MVPA was calculated according to quartile, compared with the first quartile (Q1) of MVPA, the third quartile (Q3) and fourth quartile (Q4) were associated with a reduced risk of new-onset CVD (OR=0.76, 95% CI=0.63-0.92; OR=0.81, 95% CI=0.66-0.98). The outcomes of heart diseases were similar to those of CVD. The risk of new-onset heart diseases in Q3 of MVPA was reduced by 22% compared with that in Q4 (OR=0.78, 95% CI=0.63-0.95). Conclusion MVPA may be a protective factor for CVD/heart disease, and this association may benefit more in women and older populations.